Cluster structuring of economics: world practice of building and developing clusters - Danylovych-Kropyvnytska, M. L. (Видавництво Львівської політехніки, 2014)
Establishing and developing different institutions, and encouraging their cooperation to ensure efficiency of the cluster-type structures are studied on the cases of different countries. The cluster structuring of economics that provides economic stability and sustainable growth, has become the basis of economic policies in many developed countries. The comparative studies of regional clusters, their development patterns and cooperation between businesses and the academic environment, as well as the cluster ideas promotion strategies allowed identifying three models of innovative development. Досліджено проблеми створення, розвитку та кооперації різних інституцій для забезпечення ефективності кластерних утворень на прикладі різних країн світу. Кластерна структуризація економіки, яка забезпечує стабільність економічного розвитку та ефект стійкості, стала основою економічної політики багатьох розвинених країн. Порівняльні дослідження щодо загального стану регіональних кластерів, їх розвитку, кооперації між бізнесом і академічним середовищем, політики просування кластерних ідей дають змогу виділити три моделі інноваційного розвитку
Кластерна структуризація економіки: світовий досвід створення та розвитку кластерів
Keywords: regional clusters; industrial clusters; innovation-based growth models; cooperation; cluster model of economics; регіональні кластери; промислові кластери; моделі інноваційного розвитку; кооперація; кластерна модель економіки